Differential immunological profiles in seronegative versus seropositive rheumatoid arthritis: Th17/Treg dysregulation and IL-4 - Li, Baochen; Su, Rui; Guo, Qiaoling; Su, Ronghui; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2024)
Background: Rheumatoid arthritis (RA) is an autoimmune disease with various subtypes. Among these, seronegative rheumatoid arthritis (SnRA), distinguished by its distinctive seronegative antibody phenotype, presents clinical diagnosis and treatment challenges. This study aims to juxtapose the immunological features of SnRA with seropositive rheumatoid arthritis (SpRA) to investigate potential mechanisms contributing to differences in antibody production.Methods: This study included 120 patients diagnosed with RA and 78 patients diagnosed with psoriatic arthritis (PsA), comprising 41 cases of SnRA and 79 cases of SpRA. Clinical, serological, and immune data were collected from all participants to systematically identify and confirm the most pivotal immunological distinctions between SnRA and SpRA.(1) SpRA demonstrates more pronounced T-helper 17 cells (Th17) / Regulatory T cells (Treg) dysregulation, vital immunological differences from SnRA. (2) SpRA exhibits higher inflammatory cytokine levels than SnRA and PsA. (3) Lymphocyte subset ratios and cytokine overall distribution in SnRA close to PsA. (4) Interleukin-4 (IL-4) emerges as the central immunological disparity marker between SnRA and SpRA.Th17/Treg imbalance is one of the vital immunological disparities between SnRA and SpRA. Interestingly, PsA and SnRA display similar peripheral blood immunological profiles, providing immunological evidence for these two diseases' clinical and pathological similarities. Furthermore, IL-4 emerges as the central immunological disparity marker between SnRA and SpRA, suggesting its potential role as a triggering mechanism for differential antibody production.